2006
DOI: 10.1063/1.2358990
|View full text |Cite
|
Sign up to set email alerts
|

Ion and polymer dynamics in polymer electrolytes PPO–LiClO4.II. H2 and Li7 NMR stimulated-echo experiments

Abstract: We use 2H NMR stimulated-echo spectroscopy to measure two-time correlation functions characterizing the polymer segmental motion in polymer electrolytes PPO-LiClO4 near the glass transition temperature Tg. To investigate effects of the salt on the polymer dynamics, we compare results for different ether oxygen to lithium ratios, namely, 6:1, 15:1, 30:1, and infinity. For all compositions, we find nonexponential correlation functions, which can be described by a Kohlrausch function. The mean correlation times s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 59 publications
14
36
0
Order By: Relevance
“…2 H SLR is, however, different for deuterons in the methyl groups. These results are consistent with findings in experimental work on perdeuterated PPO [33][34][35]. There, it was reported that 2 H SLR occurs in two steps, which are related to deuterons in the methyl groups and the polymer backbone.…”
Section: Conventional Spin-lattice Relaxation Analysissupporting
confidence: 94%
“…2 H SLR is, however, different for deuterons in the methyl groups. These results are consistent with findings in experimental work on perdeuterated PPO [33][34][35]. There, it was reported that 2 H SLR occurs in two steps, which are related to deuterons in the methyl groups and the polymer backbone.…”
Section: Conventional Spin-lattice Relaxation Analysissupporting
confidence: 94%
“…Also, the applicability of the BPP approach was questioned in a 7 Li spin-lattice relaxation study on hybrid organic-inorganic ion conductors [438]. In addition, 7 Li stimulatedecho experiments were used to measure the lithium ionic correlation functions for PPO-LiClO 4 at lower temperatures near the glass transition [457]. The results indicate the existence of strongly non-exponential correlation functions at variance with the BPP approach.…”
Section: Motional Narrowingmentioning
confidence: 98%
“…Also intercalation compounds based on titanium dioxide (=anatase) and titanium disulfide, i.e., Li x TiO 2 [121] and Li x TiS 2 [497][498][499] were studied in the ultra-slow domain for various Li contents, x. Finally, 7 Li stimulated-echo experiments were performed to study lithium ionic motion in polymer electrolytes [457]. In the following we will review some of these results.…”
Section: Comparing 6 LI and 7 Li Stimulated-echoesmentioning
confidence: 99%
“…[109] In general, t p can be used to set the sensitivity of an SAE NMR experiment, that is, the larger t p is chosen, and thus the larger the phase w Q t p , the better Li jumps between sites with similar EFGs can be resolved. [45,113] However, it is worth noting that in the particular case of 7 Li the preparation time t p generally should be chosen as short as possible to reduce the influence of interfering dipole-dipole interactions on S 2 (t m ). [37,52] This limitation does not necessarily hold for 6 Li (spin-1), which is subject to much smaller homonuclear dipole-dipole couplings.…”
Section: Diffusion In Confined Dimensions: LI X Tis 2 -A Model Submentioning
confidence: 99%